CONVENIENT SOFTWARE FOR BUSINESS WITH THE POSSIBILITY OF ADAPTATION TO MARKET REQUIREMENTS - PRAVORSKA, Natalya (Herald of Khmelnytskyi National University. Technical sciences, 2023)
To support day-to-day operations, business companies need flexible systems that will allow them to adapt to the markets that are changing quite quickly in today's environment. However, most of the software that exists in the market does not meet the needs of a particular company, let alone adapt to the requirements that change very quickly. Software for supporting enterprises, intended mainly for solving specific tasks. The question arises about the possibility of simplifying the development of business software, without limitations, and also being able to create custom software specifically for business, not only for use, but also for further adaptation.In business-companies, there is a need to transmit external inspection data to laboratories, as well as the possible collection of these results and combining them into research reports, which contain the results of checks on the quality and quantity of manufactured products. Usually, in order to perform such actions, it is customary for companies to use standard office programs and paper records that will allow you to conduct reviews and create various reports. In such cases, it becomes necessary to enter the same data many times in several documents. Companies are trying to find applications that can reduce such overhead and prevent errors. Since there are no existing solutions to support such activities, there is a need to create such supporting software. The task is to develop a method called "administration generation" capable of introducing a level of abstraction to reduce repetitive tasks during development. Using the Apache open-source webserver, which allows customization for a specific business-company, and the Eclipse multipurpose integrated development environment (IDE), which supports multiple development languages, including PHP and JavaScript, this method was implemented. It used the fully pluggable Symfony PHP framework combined with the highly flexible Ext JS JavaScript framework. Symfony allows you to implement the right "administrative generation" property and extensibility to meet the right current market requirements. Ext JS is currently integrating to improve the user experience. Both the first and the second are known for their excellent documentation and active community.
Keywords: software; business-sompanies; documentation; Java Script; framework; Plugin; Apache web-server; Eclipse multipurpose sntegrated development environment (IDE); Symfony PHP framework